Reactive Oxygen Species in Asthma: Regulators of Macrophage Polarization and Therapeutic Implications: A Narrative Review - Liu Y; Zhang M; Wang T; Zhang J (Journal of Asthma and Allergy)
Ying Liu,1 Mingyao Zhang,2 Tongtong Wang,3 Jun Zhang1 1School of Chinese Medicine, Anhui University of Chinese Medicine, Hefei, Anhui Province, 230012, People’s Republic of China; 2Department of Pediatrics, The Third Affiliated Hospital of Changchun University of Chinese Medicine, Changchun, Jilin, 130117, People’s Republic of China; 3The First Clinical Medical College, Anhui University of Chinese Medicine, Hefei City, Anhui Province, 230038, People’s Republic of ChinaCorrespondence: Jun Zhang, Email junzhang80122@sina.comAbstract: As a vital component of the immune system, macrophages play a critical role in the progression of asthma. The two classic polarization states of macrophages, M1 and M2, exhibit distinct functions. M1-polarized macrophages eliminate pathogens through the secretion of pro-inflammatory cytokines, while M2-polarized macrophages secrete anti-inflammatory factors to facilitate tissue repair. However, in asthma, the activation of M1 macrophages is often associated with excessive inflammatory responses, whereas M2 macrophages contribute to airway remodeling and chronic inflammation. These processes collectively exacerbate airway inflammation and remodeling, thereby aggravating asthma symptoms. Reactive oxygen species (ROS), as crucial signaling molecules, have been shown to regulate macrophage polarization and promote both M1 and M2 polarization states. This review summarizes the primary endogenous and exogenous sources of ROS in asthma and elaborates on the mechanisms by which ROS influence M1/M2 polarization of macrophages. Endogenous ROS arise chiefly from NOX2, xanthine oxidase, peroxisomes and mitochondria, whereas ozone and fine particulate matter are major exogenous sources. ROS activate MAPK, NF-κB and NLRP3 cascades, boosting IL-1β, IL-6 and IL-27 release by M1 cells, while low NOX2 flux or mitochondrial H2O2 supports STAT6-dependent ARG1 expression and drives an M2 program. Additionally, we discuss the impact of different macrophage polarization states on asthma pathophysiology and the potential applications of macrophage-modulating agents in asthma treatment, particularly those targeting ROS-mediated polarization pathways. ARG1 rich M2 cells convert L-arginine into proline, fostering collagen deposition; Ym1/2, Fizz1 and CD206 correlate with airway remodeling and declining lung function. Emerging antioxidant and macrophage-polarization strategies that selectively modulate ROS show promise in rebalancing M1/M2 responses and attenuating airway hyper-responsiveness. This review provides new insights into the interplay between ROS and macrophage polarization and highlights the potential for developing therapies aimed at modulating macrophage polarization via ROS regulation.Keywords: asthma, macrophage polarization, reactive oxygen species